Quality of Interpersonal Relationships Based on Self-Forgiveness, Other-Forgiveness and Position-Forgiveness - Hamed Kashanaki; Mohammad Ali Besharat (مجله علوم روانشناختی, 2018)
Background: Forgiveness in relationships is recognized as a factor in improving the quality of interpersonal relationships. However, the question is whether the differences in the dimensions of forgiveness as well as the different attitude towards gender roles in Iranian culture, which are different aspects of the forms of forgiveness highlighted in women and men, predict the quality of interpersonal relationships or not? And if so, what are these aspects? Aims: Based on these issue, current study aimed to investigate the relationship between types of forgiveness (self-forgiveness, other forgiveness and position forgiveness) and interpersonal problems. also it compared the interactive role of various type of forgiveness on the quality of relationships in men and women Method: Among students of University of Tehran, 154 women and 132 men responded to Dispositional Hartland Forgiveness Scale (HFS) and Inventory of Interpersonal Problems (IIP-30).  Results: Correlation and regression analysis of data showed a negative relationship between types of forgiveness and interpersonal problems (P<0/01). This relationship occurred through position-forgiveness in women (B=-0/62) and self-forgiveness in men (B=-0/56). Conclusions: In sum, the results of the present study showed gender differences in the prediction of quality of interpersonal relationship based on different types of forgiveness. In other words, interpersonal problems in men point to the lack of Self-forgiveness or criticizing to personal weaknesses and problems, while interpersonal problems in women can be indicative of situation-unforgiveness or not accepting social and cultural pressures.